Chiral Determination of Naringenin by Ultra-Performance Liquid Chromatography-Tandem Mass Spectrometry and Application in Citrus Peel and Pulp - Yao, Zhoulin; Wu, Shaohui; Zhang, Hu; Feng, Xianju; Wang, Zhen; Lin, Mei (Frontiers in Nutrition, 2022)
A chiral separation method of naringenin in citrus pulp and peel was established by ultra-performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) in this study. The liquid phase conditions for separation were Chiralpak IG-3 column at 40 ºC, mobile phase of methanol and 0.1% formic acid solution (85/15; v/v). Isovolumetric elution can complete the detection within 5 minutes. Considering the matrix effect, the matrix standard calibration curve was used for sample quantification. Quantitation was achieved by fitting a calibration curve using a standard matrix. The mean overall recoveries of the two enantiomers from orange pulp were 91.0-110.0% and orange peel were 85.3-110.3%, with relative standard deviations of 1.5-3.8 and 0.9-3.6% at the 0.5, 2.5, 50 and 250 µg/kg levels, respectively. The limit of quantification for all enantiomers in the citrus matrix did not exceed 0.5 µg/kg. Furthermore, the absolute configuration of the naringenin enantiomer was determined by combining experimental and predicted electron circular dichroism spectroscopy, and it was confirmed on a Chiralpak IG-3 column that the first eluting enantiomer was (S)-naringenin. The determination of chiral naringenin content in actual citrus samples showed that the naringenin content in hybrid citrus and citrus pulp was significantly higher than that in pomelo. The method established in this study can be used for the determination of naringenin enantiomers in citrus, which is beneficial to variety selection.